Exploring the role of granzyme B in subretinal fibrosis of age-related macular degeneration - Gill, Karanvir; Yoo, Hyung-Suk; Chakravarthy, Harshini; Granville, David J.; Matsubara, Joanne A. (Frontiers in Immunology, 2024)
Age-related macular degeneration (AMD), a prevalent and progressive degenerative disease of the macula, is the leading cause of blindness in elderly individuals in developed countries. The advanced stages include neovascular AMD (nAMD), characterized by choroidal neovascularization (CNV), leading to subretinal fibrosis and permanent vision loss. Despite the efficacy of anti-vascular endothelial growth factor (VEGF) therapy in stabilizing or improving vision in nAMD, the development of subretinal fibrosis following CNV remains a significant concern. In this review, we explore multifaceted aspects of subretinal fibrosis in nAMD, focusing on its clinical manifestations, risk factors, and underlying pathophysiology. We also outline the potential sources of myofibroblast precursors and inflammatory mechanisms underlying their recruitment and transdifferentiation. Special attention is given to the potential role of mast cells in CNV and subretinal fibrosis, with a focus on putative mast cell mediators, tryptase and granzyme B. We summarize our findings on the role of GzmB in CNV and speculate how GzmB may be involved in the pathological transition from CNV to subretinal fibrosis in nAMD. Finally, we discuss the advantages and drawbacks of animal models of subretinal fibrosis and pinpoint potential therapeutic targets for subretinal fibrosis.